Health Insurance Purchase Intention in Kathmandu - Pokhrel, Sambhavi; Phulara, Keshab Raj (Management Dynamics, 2023)
As a principal methods of financing health care, health insurance is an important risk management tool for people. This research assesses the influence of different factors on the intention to purchase health insurance. The analysis showed that most of the factors have significant positive impact on the intention to purchase health insurance among the employees. Among the factors, attitude towards purchase of health insurance and subjective norm were found to have significant direct influence on the intention. Perceived usefulness of health insurance and insurance literacy both significantly influenced the attitude towards purchase of health insurance. Also, there was found to be a significant mediation role of attitude on the influence of both perceived usefulness and insurance literacy on the intention to purchase health insurance. Referring to the findings, in order to positively influence the purchase intention of health insurance, the insurance companies and the government should consider conducting awareness programs on health and financial risk management through health insurance, aimed at positively influencing the attitudes of people towards health insurance and perceived usefulness of health insurance, and improving insurance literacy.